Exploring the Role of Tranexamic Acid in Dermatology: A literature Review - Aleksandra Górska; Natalia Gniaź; Wiktor Grela; Jagoda Niewiadomska; Daria Furtak; Dawid Tulej; Natalia Marko; Alicja Dziedzic; Dominika Marciniuk; Paulina Głogowska (Journal of Education, Health and Sport)
Introduction